Ergonomic strategies to improve radiographers’ posture during mammography activities - Cernean, N.; Serranheira, F.; Goncalves, P.; Sá dos Reis, Cláudia (2017)
Objectives: To identify alternatives for radiographers’ postures while performing mammography that can contribute to reduce the risk of work-related musculoskeletal disorders (WRMSDs). Methods: Radiographers’ postures to positioning craniocaudal (CC) and mediolateral oblique (MLO) views were simulated without any intervention for three scenarios: radiographer/patient with similar statures, radiographer smaller than patient and radiographer taller than patient. Actions were taken to modify the postures: seated radiographer; patient on a step; seated patient; radiographer on a step. All the postures were analysed using kinovea 0.8.15 software and the angles were measured twice and classified according to European standard EN1005–4: 2005. Results: The non-acceptable angles were measured mainly during MLO positioning when radiographer was taller than the patient: 139° and 120° for arm-flexion and abduction, 72° for trunk and −24° for head/neck-flexion. The introduction of alternative postures (radiographer seated), allowed improvements in posture (60° and 99° for arm flexion and abduction, 14° for trunk and 0° for head/neck flexion), being classified as acceptable. Conclusions: The alternative postures simulated have the potential to reduce the risk of developing WRMSDs when radiographers and patients have different statures. Main messages • Radiographers’ postures in mammography can contribute to work-related musculoskeletal disorders • Non-acceptable posture was identified for MLO breast positioning (radiographer taller than patient) • Adapting posture to patient biotype reduces the WRMSD risk for radiographers